From oxygen shortage to neurocognitive challenges: behavioral patterns and imaging insights - Zani, Alberto; Dishi, Yldjana; Proverbio, Alice Mado (Frontiers in Cognition, 2024)
Environmental hypoxia, resulting from reduced oxygen supply, poses a significant risk of dysfunctioning and damaging the neurocognitive system, particularly in relation to anxiety and stress. Inadequate oxygenation can lead to acute and chronic brain damage. Scholars used behavioral, hemodynamic, and electromagnetic neurofunctional techniques to investigate the effects of normobaric and hypobaric hypoxia on neurocognitive systems. They found a correlation between hypoxia, altered psychomotor responses, and changes in EEG alpha, theta, beta, and gamma rhythms, which affect spatial attention and memory. Hypoxia affects event-related potential (ERP) components differently depending on latency. Perceptual responses N1 and P2 remain largely unaffected, while the amplitudes of preattentive (MMN, vMMN), and late-latency responses (e.g., P3a), are significantly altered. Late latency components related to attention, particularly P3b, are also altered. These changes illustrate the spectrum from sensory detection to more complex cognitive processing, highlighting the brain's efficiency in managing information. Interestingly, both P3b and CNV amplitudes can increase with increased cognitive demands in hypoxia, suggesting a compensatory response. Prolonged exposure exacerbates these effects, resulting in compensatory delayed behavioural responses and alterations in behavioural monitoring and conflict inhibitory control, as reflected by reduced amplitudes in some attention-related ERP components, including N2, N2pc and ERN. Thus, neurocognitive function and integrity are under stress. ERP sources and hemodynamic images reveal that vulnerable brain regions include the frontal-prefrontal cortices, hippocampus, basal ganglia, and parietal and visual cortices, which are essential for attention-related processes like decision-making and spatial memory. The auditory system appears less affected.